Textural characteristics of oyster mushroom–soy protein extrudates and master curve of specific mechanical energy - Mohamad Mazlan, Mazween; A. Talib, Rosnita; Chin, Nyuk Ling; Shukri, Radhiah; Taip, Farah Saleena; Mohd Nor, Mohd Zuhair; Abdullah, Norazlin (HH Publisher, 2022)
The effects of screw speed and oyster mushroom (OM) addition on the texture characteristics (hardness, gumminess, and chewiness) and specific mechanical energy (SME) were determined via factorial experiment design. Increasing screw speeds alone exhibited an insignificant effect (p > 0.05) compared to the effect exhibited by OM addition. The combined effects of screw speed and OM addition significantly reduced (p ≤ 0.05) all the texture characteristics. The hardness (3521.35 g) and gumminess (2717.85) of the meat analogue extruded at the maximum screw speed of 160 rpm and 15% OM addition were close to the characteristics of the chicken breast, respectively. The OM–soy protein (SP) extrudates were chewier than the non-hydrated texturised vegetable protein (TVP) and chicken meat. The SME values of the single-screw extrusion were linearly affected by the increasing screw speed, which also lies in the range < 200 kJ/kg for producing meat analogues with acceptable characteristics. Applying the superposition technique has successfully shifted the individual curves of the SME into a smooth master curve horizontally, allowing an interpolating in the prediction of SME value at a given screw speed value. An adequate low-grade OM content and extrusion screw speed value in the SP-based meat imitation provide hardness and gumminess that resembles the chicken breast. A prediction value on the specific mechanical energy of the SP-based meat analogue extrusion may be interpolated by a given screw speed value by using an established master curve.